2005
DOI: 10.1111/j.0013-9580.2005.52504.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Epilepsy Due to Cortical Malformations: Ten‐year Follow‐up

Abstract: Summary:Children with malformations of cortical development represent a significant proportion of pediatric epilepsy surgery candidates. From a cohort of 40 children operated on between 1980 and 1992 with malformation of cortical development, 38 were alive and had data 10 years after surgery. Age at surgery ranged from 6 months to 18 years (mean, 9.6 years). Thirty-six had partial seizures, and two had infantile spasms; 20 were nonlesional. Pathologic diagnoses were cortical dysplasia (n = 31) and developmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 24 publications
4
64
0
4
Order By: Relevance
“…13,34 This could explain why surgical resection does not yield good results in the control of epilepsy in some patients with focal MCD, suggesting that the visualized MCD does not constitute the entire epileptogenic zone and that abnormalities can be found also in the perilesional as well as in the contralateral side. [35][36][37] Wieshmann et al, 38 by using diffusion tensor imaging, found reduced anisotropy affecting both hemispheres in a patient with unilateral MCD. They hypothesized that there was loss of directional organization in the contralateral white matter.…”
Section: Controls Patientsmentioning
confidence: 98%
“…13,34 This could explain why surgical resection does not yield good results in the control of epilepsy in some patients with focal MCD, suggesting that the visualized MCD does not constitute the entire epileptogenic zone and that abnormalities can be found also in the perilesional as well as in the contralateral side. [35][36][37] Wieshmann et al, 38 by using diffusion tensor imaging, found reduced anisotropy affecting both hemispheres in a patient with unilateral MCD. They hypothesized that there was loss of directional organization in the contralateral white matter.…”
Section: Controls Patientsmentioning
confidence: 98%
“…Rates of seizure freedom after resection of neoplasms have, overall, been excellent, ranging from 72% to 92% in selected series (45,63,64). The most robust predictor of complete seizure freedom across available studies has been the extent of tumor resection (61,64 (65,66).…”
Section: Temporal Lesionectomymentioning
confidence: 99%
“…The ictal onset zone is defined as the region showing focal rhythmic activity, bursts of high-frequency discharges, repetitive spiking, or electrodecremental patterns. 31 The disadvantage of scalp EEG is that in patients with FCDs there is a high incidence of widespread interictal spiking, which may obscure identification of the epileptogenic zone. 59 Hamiwka and colleagues 31 considered prominent interictal spiking to be significant if it showed consistent focality, had rhythmic features, occurred as trains of focal fast activity, or was associated with focal attenuation of background activity.…”
Section: Electroencephalographymentioning
confidence: 99%
“…In 2 long-term prospective studies, the rate of seizure freedom was Ͻ 50%, which suggests an overall decline in the rate of long-term seizure control. 31,40 Cumulative rates may be somewhat misleading as to the potential for a successful surgery in an individual patient because there are several preoperative and surgical factors that may influence seizure outcome. Temporal location of FCD lesions is associated with an 87% rate of freedom from seizures.…”
Section: Seizure Outcome After Surgerymentioning
confidence: 99%